Wooden bones - Carter, Scott William (Simon & Schuster Books for Young Readers, 2012)
Pino and his father, Gepetto, face grave danger when they are forced to go on the run after villagers learn that a puppet made by Pino to represent Gepetto's dead wife can move as Pino, himself, did before becoming a real boy.